Psychosocial health of girls and young women with UllrichTurner syndrome Psychosoziale gesundheit von mädchen und jungen frauen mit ullrich-turner-syndrom - Dörr, Helmuth-Günther; Oppelt, Patricia (Pädiatrische Praxis, 2019)
This paper gives an overview of neurocognitive, academic, social and psychological phenotypes of the UTS. In addition, the results of a survey on the life situation of young affected women in Germany after the end of growth hormone therapy are summarized using a paper questionnaire.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Growth hormone; Psychosocial health; Quality of life; UTS